Ordered growth of vanadyl phthalocyanine (VOPc) on an iron phthalocyanine (FePc) monolayer. Issue 44 (19th October 2015) - Rochford, Luke A.; Ramadan, Alexandra J.; Woodruff, D. Phil; Heutz, Sandrine; Jones, Tim S.
Abstract : A combination of LEED and STM measurements demonstrate epitaxial ordering in bilayers formed from non-planar and planar phthalocyanines. Abstract : The growth and characterisation of a non-planar phthalocyanine (vanadyl phthalocyanine, VOPc) on a complete monolayer (ML) of a planar phthalocyanine (Iron(ii ) phthalocyanine, FePc) on an Au(111) surface, has been investigated using ultra-high vacuum (UHV) scanning tunnelling microscopy (STM) and low energy electron diffraction (LEED). The surface mesh of the initial FePc monolayer has been determined and shown to correspond to an incommensurate overlayer, not commensurate as previously reported. Ordered islands of VOPc, with (1 × 1) epitaxy, grow on the FePc layer at submonolayer coverages. The individual VOPc molecules occupy sites directly atop the underlying FePc molecules, indicating that significant intermolecular bonding must occur. It is proposed that this interaction implies that the VO points down into the surface, allowing a Fe–O bond to form. The detailed appearance of the STM images of the VOPc molecules is consistent with previous studies in other VOPc growth studies in which this molecular orientation has been proposed.